Analisis Ekonomi Usaha Angkringan di Purwokerto (Studi Kasus Usaha Angkringan di Kecamatan Purwokerto Utara) - Jamil, Harun Nur; Setiarso, Oke; Windhani, Kikin (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
The present study is entitled “Economical Analysis among Street Food Vendors (Angkringan) in Purwokerto, Indonesia: The Case of Angkringans in North Purwokerto”. The research question deals with the sum of profits and its financial efficiency of the food vendor management. Specifically, the study is aimed at investigating how much the profit is gained and how economical its efficiency is among the vendors. This study is based on prime data generated from interview and questionnaires administered to the food vendor owners. The total number of subjects in the study 15 street food vendors in North Purwokerto. The study was carried out from 30 July to 12 November 2018. Data analysis was focused on income generated, cost and benefit, and its economic efficiency. Findings of the study indicated that the highest profit among the 15 street vendors was Rp 5.942.000 (IDR 5,942,000) per month and Rp - 4.269.000 (IDR 4,269,000) was the least. Out of the total number of 15 vendors, 11 (73%) got expected profits, and the rest, 4 (27%) lost its profits. Level of economic efficiency of its profits among 15 vendors reached 1,26%/month (the most) and 0,70 (the least). In other words, out of the total number of the vendors, 11 (73%) indicated its efficiency and 4 (27%) showed inefficiency. Implications of the study to the management of the street vendors that lost their profits are concerned with the way how to manage financial accounts, considering its feasible locations, and efficiently managing raw materials. Thus, good management of vendors is urgently needed to pursue balanced profits to consider the feasibility of the food vendor entrepreneurship.